Establishment of criteria for quality evaluation system of basic research funding at Viet Nam national foundation for science and technology development - Nguyen Thi Phuong (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
Exploratory factor analysis (EFA) and Confirmatory factor analysis (CFA) was employed to examine the quality scale of basic research funding at the National Foundation for Science and Technology Development in Vietnam. The research results have determined the basic research funding quality scale with 6 components: (1) Relevancy; (2) Funding effectiveness; (3) Funding efficiency; (4) Impact sponsorship activities; (5) Sustainability of sponsorship; and (6) results achieved after sponsorship with 29 observed variables. The research results provide a theoretical model for the evaluation scale of basic research funding quality for further studies, and at the same time provide a basis for evaluating the quality of basic research funding at the National Foundation for Science and Technology Development in Vietnam. Code: 21121402